Analysis of a Railway Vehicle with Unevenness on Wheel - Loulova, Maria; Suchanek, Andrej; Harusinec, Jozef; Strazovec, Peter (Manufacturing Technology Journal, 2018)
One of the basic principles of railway vehicles is their carrying and guiding. In the contact pair of a wheel and a rail, one body is rolled on the surface of the other part and all main forces are transmitted in this contact. Contact between wheel and rail is also important from an economic aspect as it is related to the wear of the track rails and the wheel thread itself, including the wheel flange, and has caused the necessary maintenance of the track and the vehicles themselves. Therefore, our article focuses on simulating the influence of a flat wheel on changes in wheel forces. The model was created in the CATIA program and was consequently imported into the SIMPACK program, which was followed by analysis of the passage of the vehicle along the track. In the simulation, we considered an ideal track and a wheel flat on the right front wheel. We also plan to work with these results by adding and comparing them with results obtained by applying irregularity to our ideal track.
Keywords: Wheel flat; simulation; rail - wheel contact; safety against derailment